The Influence of Heat Treatment on the Microstructure and Hardness Properties of Ti6Al4V and MgAZ91D Alloys / Yusliza Yusuf...[et al.] - Yusuf, Yusliza; Jaafar, Abdul Rahim; Omar, Noririnah; Azlan, Umar Al Amani (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Ti6Al4V alloy and MgAZ91D alloy have excellent combinatorial properties. However, in many cases their applications are limited because of weaknesses in their mechanical properties such as low fatigue strength for MgAZ91D and low modulus elasticity for Ti6Al4V. In this work, the proposed solution is to improve their hardness properties by applying the suitable heat treatment process on these alloys. The heat treatment temperature of Ti6Al4V was performed at 950oC and 900oC, while for MgA91D at 500oC and 450oC. This is followed by water and air quenching and aging treatment at 400oC/4 hours for Ti6Al4V and 200oC/8 hours for MgAZ91D. The results show that the heat treatment process with water quenching medium helps to improve the properties of Ti6Al4V and MgAZ91D alloy in terms of microstructure's changes and generally the value of hardness and roughness was increased after the heat treatment process.